Multidisciplinary Rehabilitation and Climatotherapy for Chronic Diseases at the Dead Sea - Dramsdahl, Elisabeth (Anales de Hidrología Médica, 2012)
Introduction: Since 2004, the DMZ Medical Center and the Norwegian Rehabilitation Center are providing multidisciplinary and comprehensive program for patients suffering from various chronic conditions, mostly musculoskeletal diseases and Chronic Fatigue Syndrome (CFS). The Center has developed a unique concept, based on a multidisciplinary rehabilitation model associated to the intense use of climatic factors present in this area, offering so a good alternative for Norwegian patients. The multidisciplinary rehabilitation Climatotherapy (MDR-C) at the Dead Sea fit the needs of a true MDR program, while introducing a new dimension in this field. Methods: This 3-week long multidimensional rehabilitation at the Dead Sea is a full-time behavioral medical program administered in a cognitive out-patient setting which follows the evidence-based guidelines for therapeutic interventions. At the Dead Sea, medical and psychiatric co-morbidities are carefully taken into account when tailoring the therapeutic plan for each patient. As well the nature and severity of symptoms, together with the individual’s level of function and psychosocial stressors of each participant are initially evaluated, before and during the treatment. Several psychological, cognitive and psychosocial interventions are included in this MDR-C program, resulting in a very compact and powerful multi-modal cognitive behavioral agenda. Results and Conclusion: Of more of thousand patients treated, a huge amount of them showed significant improvement in their condition and quality of life parameters after treatment at the Dead Sea, describing their stay as a turning point in their disease history and in their life. In a large proportion, they were able to resume work, education or studies. Norwegian physicians are now referring in increasing numbers chronically ill patients to this intensive rehabilitation program.